Optimizing teachers’ role in developing responsibility as a social skill of autistic children in inclusive schools - Salsabila, Annisa Zahra; Junaidi, Ahsan Romadlon; Ediyanto; Hastuti, Wiwik Dwi; Novianti, Ranti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Autistic children often face challenges in various aspects of social skills, particularly in demonstrating responsibility including difficulties in understanding emotional expressions, building relationships, and adapting to social norms. Inclusive education plays a crucial role in fostering their social skills, with teachers serving as primary facilitators. This study aims to explore the strategies teachers employ in guiding autistic children and identify the challenges encountered in inclusive kindergarten settings. A descriptive qualitative research method was utilized, incorporating observation, interviews, and document analysis. The data analysis process consists of three main stages, namely data reduction, data presentation, and conclusion drawing. The findings reveal that teachers implement various strategies, such as role-playing, social storytelling, and positive reinforcement, to enhance the social skills of autistic children. However, several challenges persist, including limited specialized training, difficulties in balancing attention between regular and special needs students, and classroom management complexities. Therefore, greater support from schools and parents is essential to establishing a more inclusive and conducive learning environment that promotes the social development of autistic children.